A low-cost lab-on-a-chip device for marine pH quantification by colorimetry - Pinto, Vânia Cristina Gonçalves (2019)
Supplementary material related to this article can be found, in the online version, at doi:https://doi.org/10.1016/j.snb.2019.03.098.